Classification and Nomenclature of the Sandpipers (Aves: Arenariinae) - Banks, Richard C. (Zootaxa, 2010)
The sandpipers, stints, knots, turnstones, and closely related shorebirds known by a variety of distinctive English group names are so widely diverse in morphology, behavior, and ecology that 26 species have been classified under no fewer than 19 available generic names. The two species of turnstones in the genus Arenaria are sufficiently distinctive as to have been treated as a family-group (International Commission on Zoological Nomenclature [ICZN] 1999, Art. 35, 36)—Arenariidae, Arenariinae, or Arenariini, depending on taxonomic viewpoint. The Surfbird, in the monotypic genus Aphriza, was included in that family-group until Jehl (1968) showed that it is more closely related to the “typical” sandpipers. As such, it became one of five distinctive monotypic genera allied with the large polytypic genus Calidris in the family-group Calidrididae, Calidridinae, or Calidridini (e.g., American Ornithologists’ Union [AOU] 1983, 1998; Dickinson 2003, Gill and Wright 2006; see Jehl 2010). Calidris had early on become the senior synonym of 14 generic names in this group of 23 species (see synonymies in Peters 1934, Hellmayr and Conover 1948, AOU 1998), some of which were already senior to other generic names (see Ridgway 1919).